Cluster-randomized crossover trial of chlorhexidine–alcohol versus iodine–alcohol for prevention of surgical-site infection (SKINFECT trial). Issue 5 (20th May 2019) - Charehbili, A; Koek, M B G; Mol van Otterloo, J C A; Bronkhorst, M W G A; Zwaal, P; Thomassen, B; Waasdorp, E J; Govaert, J A; Bosman, A; Bremer, J; Ploeg, A J; Putter, H; et al.
Abstract: Background: Surgical-site infection (SSI) is a serious surgical complication that can be prevented by preoperative skin disinfection. In Western European countries, preoperative disinfection is commonly performed with either chlorhexidine or iodine in an alcohol-based solution. This study aimed to investigate whether there is superiority of chlorhexidine–alcohol over iodine–alcohol for preventing SSI. Methods: This prospective cluster-randomized crossover trial was conducted in five teaching hospitals. All patients who underwent breast, vascular, colorectal, gallbladder or orthopaedic surgery between July 2013 and June 2015 were included. SSI data were reported routinely to the Dutch National Nosocomial Surveillance Network (PREZIES). Participating hospitals were assigned randomly to perform preoperative skin disinfection using either chlorhexidine–alcohol (0·5 per cent/70 per cent) or iodine–alcohol (1 per cent/70 per cent) for the first 3 months of the study; every 3 months thereafter, they switched to using the other antiseptic agent, for a total of 2 years. The primary endpoint was the development of SSI. Results: A total of 3665 patients were included; 1835 and 1830 of these patients received preoperative skin disinfection with chlorhexidine–alcohol or iodine–alcohol respectively. The overall incidence of SSI was 3·8 per cent among patients in the chlorhexidine–alcohol group and 4·0 per cent among those in the iodine–alcohol group (odds ratio 0·96, 95 per cent c.i. 0·69 to 1·35). Conclusion: Preoperative skin disinfection with chlorhexidine–alcohol is similar to that for iodine–alcohol with respect to reducing the risk of developing an SSI. Graphical Abstract: Chlorhexidine–alcohol was compared with iodine–alcohol in a large prospective study. No superiority was found for chlorhexidine–alcohol. All things are better with alcohol!